Análisis de riesgo biomecánico de los puestos de trabajos de la empresa Servioptica S.A.S de Santa Marta, Magdalena (2022)
The objetive of this degree Project is to have an identification in the jobs in the Servioptica company SAS Magdalena, about the ergonomic risks that could be found, in which it was possible to demonstrate through various methods that have been endorsed both nationally and internationally, from which the level of criticality that can be had in the different areas where employees are subjected when fulfilling their working hours within the company is measured. In this analysis of the ergonomic risks found in the workstations of the aforementioned organization, the second update of the risk matrix (GTC 45) Colombian technical guide was used, with which it was possible to identify which were the ergonomic risks with those who were being counted, so that with this, the level they are having in the exhibition of their jobs can be determined; this, by means of the classification and the values that the GTC 45 has established. After that, an evaluation is carried out using methods such as Rosa and Rula, to analyze the data that shows that there are problems of the different health conditions that exist in the jobs at the Servioptica company. SAS del Magdalena; with which it was possible to give results in these diseases within working hours such as: repetitive movements, bad positions, lack of active breaks, data visualization. Thus, finally, upon obtaining said diagnosis in the area of ergonomics in the evaluated company, a proposal was made to give control to the diseases that are being caused by musculoskeletal in the workplace with the areas where more critical risks are they were able to identify.